VECROsim Dataset - Xun Zhang (22525487) (2025)
The dataset released as part of the VECROsim paper provides a comprehensive collection of multi-modal observability data - metrics, logs, and distributed traces - captured from a microservice-based system under both normal and fault-injected conditions. Designed to support research on performance analysis, failure characterization, and anomaly detection in microservices, the dataset includes diverse fault types, controlled scenario variations, and rich system telemetry. This makes it a valuable benchmark for evaluating system reliability and diagnostic techniques.